The effect of amalgam alloy types, surface treatments, and bonding agents on the shear bond strength between amalgam and resin composite - Raghad A. Rasheed; Abdul-Haq A. Suliman (University of Mosul, College of Dentistry, 2006)
Aims: To evaluate the effect of amalgam alloy types, surface treatments, bonding agents, on the shear bond strength between set amalgam and resin composite restorative materials. Materials and Methods: Three hundred and thirty eight holes (6 mm in diameter and 2 mm depth) prepared in a 2x2.5 cm cold cure acrylic resin blocks in which amalgam was condensed. The 338 samples were divided into two groups, the control group which consisted of 26 intact amalgam samples, and the repair group consisted of 312 repair amalgam samples. Each group (intact, and repair) was subdivided into two groups according to the type of amalgam alloy. Half of the samples were filled with spherical amalgam alloy and the other were filled with admixed amalgam alloy. The repair samples then divided in to four groups according to the surface treatment, in turn each sub-group divided into three groups according to the bonding agent. The samples were thermocycled, before shear bond strength was tested. The mode of failure was observed for each specimen. Results and Conclusion: The statistical analysis showed that the repair strength was 50% of the intact strength, and the admixed amalgam samples showed higher shear bond strength than spherical amalgam samples. The group roughened with diamond bur showed higher repair bond strength than the groups received other surface treatment. The use of dentin bonding agent (All-Bond 2 and Alloybond) would increase the repair bond strength between the amal